Pengaruh Mazhab Naḥwu Kūfah dalam Kitab Matn al-Ājurrūmīyah - Andi Holilulloh (Al-Ma‘rifah, 2020)
The school (madhhab) of Kūfah had given a lot of influences on the development of naḥwu, including the use of terms. This study uses a qualitative method and the result indicates that there are many terms in the school of Kūfah used in the book of al-Ājurrūmīyah, including (1) the use of term al-khafḍ for i‘rāb al-ism is written with kasrah, not in the term al-jarr; (2) the use of term al-maf‘ūl al-ladhī lam yusamma fā‘iluh for the term subject in a passive verb, not using the term nā’ib al-fā‘il; (3) the use of term kayfamā is part of al-af‘āl al-jawāzim or from ‘āmil (particle) which can place a fi‘l muḍāri‘ into the jussive mood (majzūm), as the Kūfah scholars believe it; (4) The signs of ism are the entry of alif and lām as believed by the scholars of the Kūfah, while according to the scholars of Baṣrah it is based on the rules of alif and lām; (5) the use of term al-na‘t, not al-ṣifah; (6) al-asmā’ al-khamsah means abūka, akhūka, ḥamūka, fūka, dhū māl, but the scholars of Baṣrah believe that al-asmā’ al-sittah is by adding one ism, namely hanūka.